2016
DOI: 10.1111/cge.12886
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 mutation testing in Cyprus; a population based study

Abstract: This paper presents the largest study in Cyprus evaluating the frequency and distribution of BRCA1/2 mutations in a high risk patient cohort. Deleterious mutations in the BRCA1/2 genes were identified in 68 of the 527 patients tested (13%). It is of interest that a quarter of those tested positive, did not have an extensive family history of breast/ovarian cancer but were diagnosed with early onset breast cancer, ovarian cancer under the age of 60 or triple negative breast cancer. The spectrum of mutations ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Results obtained in our cohort corroborate the previously reported studies that investigated only BRCA genes within familial patients [26]. Of the 11 germline mutations, we identified 10 sequence variants in BRCA1 and BRCA2 genes, including 13.95% (6/43) cases carrying a pathogenic mutation and the frequency correlate strongly with Cyprus study that reported a similar clinical yield of 13% for BRCA genes [27]. Despite of small cohort size, we have found germline pathogenic mutation impact on BRCA2 (9.30%, 4/43) which is approximately 2-fold higher than BRCA1 (4.65%, 2/43), suggesting that BRCA2 is frequently mutated or altered in our cohort.…”
Section: Discussionsupporting
confidence: 89%
“…Results obtained in our cohort corroborate the previously reported studies that investigated only BRCA genes within familial patients [26]. Of the 11 germline mutations, we identified 10 sequence variants in BRCA1 and BRCA2 genes, including 13.95% (6/43) cases carrying a pathogenic mutation and the frequency correlate strongly with Cyprus study that reported a similar clinical yield of 13% for BRCA genes [27]. Despite of small cohort size, we have found germline pathogenic mutation impact on BRCA2 (9.30%, 4/43) which is approximately 2-fold higher than BRCA1 (4.65%, 2/43), suggesting that BRCA2 is frequently mutated or altered in our cohort.…”
Section: Discussionsupporting
confidence: 89%
“…We focused our study on variant detection rates and genetic characteristics associated with specific selection criteria for BRCA1/2 testing in high-risk families and patients affected by breast cancer, whereas other authors evaluated clinical implications and strategy of surveillance of women at high risk. Thirteen percent of the individuals evaluated were carriers of a pathogenic variant, according to the range shown in other countries [ 27 , 28 , 29 , 30 ], excluding Ashkenazi Jewish ancestry in which founder variants were prevalent [ 31 ]. The incidence of BRCA1 and BRCA2 variants was 7.7% and 6.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The clinicopathological and prognostic characteristics of patients with ovarian cancer in Cyprus are currently not well understood. While there are a few studies in the literature that explore hereditary ovarian cancer and gene mutations of BRCA1 and BRCA2 [32][33][34], research specifically focusing on the prognostic factors of ovarian cancer has not been conducted in Cyprus. Thus, the aim of this study was to investigate and examine the factors that are linked to the overall survival (OS) and progression-free survival (PFS) of individuals diagnosed with ovarian cancer in the republic of Cyprus.…”
Section: Introductionmentioning
confidence: 99%